Cover Image, Volume 118, Number 11, November 2021. Issue 11 (13th October 2021) - Sung, Jae‐Yoon; Lee, Yong‐Jik; Cho, Yong‐Joon; Shin, Myeong‐Na; Lee, Sang‐Jae; Lee, Han‐Seung; Koh, Hong; Bae, Jin‐Woo; Shin, Jae‐Ho; Kim, Hyun Jung; Lee, Dong‐Woo
Abstract : The cover image is based on the Article A large‐scale metagenomic study for enzyme profiles using the focused identification of the NGS‐based definitive enzyme research (FINDER) strategy by Jae‐Yoon Sung et al., https://doi.org/10.1002/bit.27904 .